On Wijsman (f, I) -Lacunary Statistical Convergence of Order ? - Sengul, Hacer; Et, Mikail; Cakalli, Huseyin (Amer Inst Physics, 2019)
In this paper we introduce the concepts of Wijsman (f, I) -lacunary statistical convergence of order alpha and Wijsman strongly (f, I) -lacunary statistical convergence of order alpha, and investigated between their relationship.
International Conference of Mathematical Sciences (ICMS) -- JUL 31-AUG 06, 2018 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Sequences; series; summability; functional analysis